Islamic Religious Education (PAI) History Learning Innovations - Fauziah, Meli (STAI Miftahul Ula Nganjuk, 2024)
The purpose of this study is to evaluate the effectiveness of educational films as a learning medium in deepening students' understanding of Islamic Cultural History and improving their critical thinking. This research method uses a qualitative approach with descriptive analysis. Data was collected through observations and interviews. Constructivism theory is used as a theoretical foundation to understand how educational films can help students relate new knowledge to their everyday experiences. The results of the study show that the use of educational films significantly increases students' interest in learning, critical thinking and involvement in the learning process. Students showed an increased understanding of PAI's history and stated that the film made the material more engaging and easier to understand. The recommendation of this study is that the PAI curriculum in elementary schools should make more use of educational film media as a learning aid. In addition, educators need to be trained in the use of new technologies and media to create a more engaging and interactive learning environment. Thus, the use of educational films can be an innovative strategy in improving the quality of PAI history learning, and facilitating a deeper and more meaningful understanding of the material taught.